PENGARUH MINAT BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN TIME TOKEN TERHADAP HASIL BELAJAR AKUNTANSI - Purida Alawiyah Simbolon; Harningsih Fitri Situmorang (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The learning model used is Time Token. This research aims to: (1) Find out the influence of interest in learning using the Time Token Learning Model on Accounting Learning Outcomes in Class X of SMK Tritech Informatika. (2) Knowing student learning outcomes using the Time Token Learning Model in Class X of SMK Tritech Informatika. The type of research used was experimental and the research subjects used were class X Accounting students at SMK Tritech Informatika. The research instruments used were learning results tests and questionnaires. The test questions in the form of essays and questionnaires have been tested and declared valid and reliable. The results of testing the research hypothesis through a simple linear regression test show that the t value is 2.318 and by comparing the t table value of 1.724, it is 2.318 > 1.724 so the decision is that Ha is accepted and Ho is rejected. This means that there is an influence of interest in learning using the Time Token learning model on accounting learning outcomes in class X at SMK Tritech Informatika